The Swiss common garden network: testing assisted migration of tree species in Europe - Streit, Kathrin; Brang, Peter; Frei, Esther R. (Frontiers in Forests and Global Change, 2024)
A warmer climate with drier summers will affect the suitability of tree species in their current range in most of Europe. To preserve ecosystem services in the future, many European countries are looking for tree species adapted to the expected future climate and are setting up trials to test them in different environments. In collaboration with forest practitioners and federal and regional authorities, we have established a network of 57 common gardens across large environmental gradients in Switzerland. Over a period of 30 to 50 years, the vitality, growth and survival of 18 tree species from 117 seed sources will be monitored to develop tree species recommendations for forest managers. In this article, we outline the considerations, challenges and trade-offs involved in designing this experiment, as well as the participatory process with a variety of stakeholders, from local foresters to the Federal Office for the Environment. Further, we list experiments testing multiple species on multiple sites in Europe and compare experimental designs, tree species and environmental gradients. The Swiss common garden network complements other European experiments and broadens the potential network by extending the covered environmental gradients to colder and moister conditions. Such targeted assisted migration trials are key to promoting tree species that can cope with the future climate and can help us to foster forest ecosystems that can adapt to rapidly changing climates.